Efeito vinculante dos precedentes, segurança jurídica e prestação jurisdicional como garantia fundamental - Lopes, Márcio Marçal (2012)
This paper starts with a discussion of theoretical assumptions related to the theme to be developed: a discussion of the judiciary, the service court and the tendency of \"exaltation\" of judicial precedent as a legal source, implies a necessary overview of the classical school the right of common law and civil law, which are constantly submerged in a mutual process of convergence, the result of man\'s search for a society and socio-legal system more secure, efficient, quick and in the end, just. Thus, in the first part of this paper, we will weave this author held a discussion on the history and construction of the family of common law and civil law, starting with the first, so that some assumptions are set for the subsequent analysis . Even Start, will highlight the formation, structure, sources and key milestones such schools legal categorization, brief comparison between the main countries that have adopted one or another system, etc. Enter will be still a more accurate reflection of the influence brought about by the common law and how that immanence has been reflected on the jurisdictional activity practiced by the judiciary in Brazil, especially with regard to the hereafter \"verticalization of the jurisdiction , \"described as the motion of granting increasing powers and duties of the higher courts, often at the expense of functional autonomy and freedom of conscience tyrannical courts and lower level. More than that, it is objective of this paper to trace some of the inevitable reactions found in the legal vertical to that, sometimes to the benefit, sometimes to the detriment of the protection of fundamental rights. Parallel to this, even by way of introduction, there is no way to move away from some institutions and principles, which were and are of fundamental importance for the analysis of judicial power, articulated by thinkers and jurists who have greatly contributed to the construction of the history of man , society and the state itself, such as Montesquieu and Hans Kelsen, who contributed greatly to the dissemination of the discussion of the theory of \"tripartition of powers\" and \"legal positivism\", respectively, issues inextricably linked to the evolution of judicial power. In the middle of the road ahead will be treated part of the legal and procedural tools created over the last decades (some of questionable constitutionality), all with the ultimate goal of making the process less bureaucratic and more quickly, giving almost absolute judicial source effects. This trend has noble foundations, as now cited, however, the proposed means for achieving these goals is open to criticism. This point is of crucial importance for the conclusions reached by this work. From this perspective, we pass by the analysis (albeit with aim of example) of comparative law, telling the paper that the case law has had in jurisdictions such as Portuguese, Italian, among others, when effectively achieve the tools and positions taken by the higher courts in Brazil, which have represented the \"government\" of the case law in the construction of state and society, with a marked increase in regulatory activity. In the final analysis, to allocate a very controversial issue: the overcoming of the foregoing, translated into face-law and the effects that such conduct may result in court, especially in a frank context of law and judicialization of preponderance of the right precedent. So, you want the job go a little further than the mere observation of the influence of the thought of the last bodies from the judiciary, as it raises demonstrate the necessary caution with which the evolution should be treated, lest it be in Indeed, back in the constitutional function of the state of social peace, the great part played by the judiciary. At the end, considerations about the process of overcoming the legal precedents are measured and their effects (beneficial or not) to the daily life of jurisdictions, as well as an opportunity to talk about legal certainty and good faith of the Government, as well as fundamental rights the citizen. By way of a preliminary conclusion, the author brings some reflections on the problems raised, whose highest aim is not to exhaustion, but that foster discussion, so that the same moose new heights.